Learning Strategies for Islamic Religious Education Teachers in Increasing Student Learning Interest at SMK S YWKA Medan - Nabillah Putri (Al-Ulum: Jurnal Pendidikan Islam, 2023)
This study aims to determine students' interest in learning in Islamic Religious Education subjects and teacher strategies in the learning process to increase student interest in learning in Islamic subjects at SMK S YWKA Medan. This type of research is descriptive qualitative, namely research that reveals facts in the field with observations and interviews and uses library data.  (Evinna Cinda Hendriana 1), 2016) Sources of data obtained from all residents of SMK S YWKA Medan which includes teachers and students. Research data were collected through observation and interviews. The results showed that the strategies used by teachers in increasing students' interest in learning varied greatly, such as using discussion strategies, question and answer, and others. However, in practice there are still shortcomings because teachers still use the lecture method every time they start the learning process. When it comes to interest in learning, students at SMK S YWKA MEDAN are very interested in learning more about PAI subjects even though there are still students who are slow in understanding these subjects.